2001
DOI: 10.1046/j.1365-4362.2001.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study to determine the efficacy and safety of 1% methotrexate/Azone® (MAZ) gel applied topically once daily in patients with psoriasis vulgaris

Abstract: The efficacy and safety of an Azone‐enhanced topical gel formulation of 1% methotrexate (MAZ), administered once daily for 8 weeks, was compared with that of placebo vehicle for the treatment of severe plaque psoriasis. Fifty‐three patients were involved in this double‐blind, paired‐comparison study. Changes in disease signs and symptoms indicated that both agents have antipsoriatic activity; however, lesions treated with MAZ exhibited significantly greater improvement. At the end of treatment, 27% of MAZ‐trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 4 publications
0
35
2
1
Order By: Relevance
“…Progress was evaluated on a weekly basis by a group of physicians in terms of improvement in Psoriasis Area and Severity Index (PASI) score, Overall Lesion Severity Scale (OLS), Physician's Assessment (PA), Psoriasis Symptom Assessment (PSA) and Safety and Tolerability Assessment (STA) (Lynda Sutton, 2001). The PASI score was calculated as the sum of the severity of the main symptoms multiplied by the numerical value of the area involved with various percentages of the 3 main body areas.…”
Section: Clinical Studymentioning
confidence: 99%
“…Progress was evaluated on a weekly basis by a group of physicians in terms of improvement in Psoriasis Area and Severity Index (PASI) score, Overall Lesion Severity Scale (OLS), Physician's Assessment (PA), Psoriasis Symptom Assessment (PSA) and Safety and Tolerability Assessment (STA) (Lynda Sutton, 2001). The PASI score was calculated as the sum of the severity of the main symptoms multiplied by the numerical value of the area involved with various percentages of the 3 main body areas.…”
Section: Clinical Studymentioning
confidence: 99%
“…Previously various formulation strategies and enhancement techniques have been used to enhance the transdermal delivery of MTX (Vaidyanathan, Chaubal, and Vassarada 1985;Alvarez-Figueroa, Delgado-Charro, and Blanco-Mendez 2001;Sutton et al 2001;Wong et al 2005;Vemulapalli et al 2008). Tiwari et al (2003) studied the clinical efficacy of MTX by means of iontophoresis and suggested that a short application of current is sufficient for the treatment of psoriasis.…”
mentioning
confidence: 99%
“…Being water-soluble and negatively charged, MTX is not readily transported into the skin by passive diffusion. The clinical response is also limited when MTX is topically applied [16]. In the present study, we used two physical techniques, a lowfluence Er:YAG laser and electroporation, to enhance the skin permeation of MTX.…”
Section: Discussionmentioning
confidence: 99%